2006
DOI: 10.1158/1078-0432.ccr-05-2587
|View full text |Cite
|
Sign up to set email alerts
|

ABCA3 as a Possible Cause of Drug Resistance in Childhood Acute Myeloid Leukemia

Abstract: Background: A major issue in the treatment of acute myeloid leukemia (AML) is resistance to chemotherapeutic drugs. Multidrug resistance can be caused by ATP-binding cassette (ABC) transporters that function as drug efflux pumps. The majority of these proteins have not yet been examined in malignant diseases. Experimental Design: A newly developed microarray for the simultaneous quantification of 38 ABC transporter genes and Taqman real-time PCR was used to analyze the expression of ABC transporters in pediatr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 23 publications
2
66
1
2
Order By: Relevance
“…However, correlation analysis between ABC transporter expression and the clinical outcome did not generate any statistically significant differences in the ALL. Although ABCA3 knock-down in the osteosarcoma cell line 143B by siRNA appeared to generate a significant increase in cellular sensitivity to Adriamycin [33,35], it did not result in any survival effect in response to vinblastine and methotrexate. Knock-down of ABCA2 alone in 143B cells did not appear to have any effect on survival in response to Adriamycin, vinblastine, or methotrexate.…”
Section: Identification Of Abc Transporter Genes In Drug-selected Celmentioning
confidence: 86%
See 2 more Smart Citations
“…However, correlation analysis between ABC transporter expression and the clinical outcome did not generate any statistically significant differences in the ALL. Although ABCA3 knock-down in the osteosarcoma cell line 143B by siRNA appeared to generate a significant increase in cellular sensitivity to Adriamycin [33,35], it did not result in any survival effect in response to vinblastine and methotrexate. Knock-down of ABCA2 alone in 143B cells did not appear to have any effect on survival in response to Adriamycin, vinblastine, or methotrexate.…”
Section: Identification Of Abc Transporter Genes In Drug-selected Celmentioning
confidence: 86%
“…The same array was also used to profile ABC transporter expression and its correlation to clinical responses of 42 childhood acute myeloid leukemia (AML) patients [33]. It was found that, of all 38 human ABC transporters examined, only ABCA3 had significant correlation of over-expression to poor response ( Table 4), suggesting that ABCA3 may contribute to clinical drug resistance in AML.…”
Section: Identification Of Abc Transporter Genes In Drug-selected Celmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Likewise, drug-resistant variants of human T-lymphoblastic cell lines displayed an increase in ABCA3 expression levels in comparison with the parental lines, in this study due to transcriptional upregulation. 26 Furthermore, utilizing RT/PCR Steinbach et al 27 detected ABCA3 expression in a cohort of 42 pediatric AML samples, and reported significantly higher levels of ABCA3 in 21 patients with poor treatment outcome, compared to 21 patients who benefited from chemotherapy. Finally, in addition to the data of this report, significant ABCA3 expression was identified in cells of epithelial neoplasms such as neuroblastoma and breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The data suggest that drug-effluxmediated drug resistance of leukemic stem cells may be conferred by many members of the ABC family of membrane transporters with possibly promiscuous action on different chemotherapeutical compounds. The conserved expression of many members of the ABCA family and their emerging role in drug resistance 70 could be of particular importance in this regard and warrants future investigations to further elucidate the role of this class of transporters in drug resistance.…”
Section: Abcb1 and Abcg2 In Drug Resistance Of Aml Cd34 þ 38à Hematopmentioning
confidence: 99%